Peran Kader Pembangunan Manusia Dalam Pencegahan Stunting di Desa Mekarjaya Kecamatan Cikalongwetan Kabupaten Bandung Barat - Setiawan, Agustina; Rokhmat, Dicky Febriansyah; Ristala, Harky; Haikal, Ridwansyach As; Daeli, Panca Ricci Richardo Immanuel; Ramdani, Wisam (Journal of Indonesian Rural and Regional Government, 2025)
This study aims to analyze the role of Human Development Worker (Kader Pembangunan Manusia or KPM) in preventing stunting in Mekarjaya Village, where an effective strategy has not yet been fully established. Although the Mekarjaya Village Government has formed KPMs, their roles are considered suboptimal due to various constraints in planning, implementation, and evaluation. The research employs a descriptive method with a qualitative approach. Data were collected through in-depth interviews and document analysis. The findings indicate that the role of KPMs in Mekarjaya Village has become increasingly optimal in efforts to prevent and address stunting. This optimal role is aligned with the duties and functions stipulated in the Village Decree of Mekarjaya No. 141.3/Kep-06/I/2025 concerning Human Development Worker. Empirically, KPMs play a vital role in stunting prevention by actively engaging in socialization, convergence, data collection, and facilitation of prevention and treatment efforts, resulting in no new stunting cases reported in 2025. The effectiveness of KPM performance is supported by strong coordination and collaborative networks involving the Family Assistance Team (TPK), Posyandu cadres, the Indonesian Ulema Council (MUI) representatives, midwives, the Health Office, the Family Planning Unit (UPTD KB), and neighborhood-level cadres (RT/RW). Furthermore, the Village Government provides intensive support, including IT facilities, updated health measurement tools, and capacity-building programs. However, despite these positive developments, challenges remain, particularly the limited number of KPM personnel currently only one person and the incomplete coverage of program socialization among school students.